Green roof and green wall benefits and costs: A review of the quantitative evidence. (January 2021) - Manso, Maria; Teotónio, Inês; Silva, Cristina Matos; Cruz, Carlos Oliveira
Abstract: Greening the urban environment can be an important strategy to tackle the problems of urban densification and meet the United Nations Sustainable Development Goals. Green infrastructures, like green roofs and green walls, have multiple associated environmental, social and economic benefits that improve buildings performance and the urban environment. Yet, the implementation of green roofs and green walls is still limited, as these systems often have additional costs when compared to conventional solutions. Recent studies have been comparing these greening systems to other solutions, balancing the long-term benefits and costs. Also, there is significant research on green roofs and green walls benefits. Although, green roofs and green walls economic analyses don't include all benefits due to measuring difficulties. The associated uncertainty regarding the quantification of the benefit makes it difficult to compare the research outcomes. This paper aims to provide a research review of existing benefits and costs of different types of green roofs and green walls. These were divided between building scale benefits, urban scale benefits and life cycle costs, focusing on the identification of results variability and assessment of their average quantification. The analysis shows that in general, there are few data regarding intangible benefits, as the promotion of quality of life and well-being. Also, there are still few studies quantifying green walls benefits and costs. High variability in data is mostly related to the different characteristics of systems, buildings envelope, surrounding environment and local weather conditions. Highlights: Review of existing research on green roofs and green walls benefits and costs. Focus on building scale benefits, urban scale benefits and life-cycle costs. Variability identification and average quantification assessment. Fewer studies have quantified green walls benefits and costs. There is high variability in data across all benefits and costs.